1996
DOI: 10.1515/jpme.1996.24.3.287
|View full text |Cite
|
Sign up to set email alerts
|

Growth and development in preterm infants receiving fluoroquinolones

Abstract: Growth and development were followed in 7 preterm newborn infants who received fluoroquinolones in the neonatal period. Quinolones were used as a "life saving" therapy in cases of sepsis caused by bacterial agents sensitive only to these drugs. Two other groups of neonates matched for gender, birth weight and gestational age served as controls. Although the quinolone group had more severe illness, no statistically significant differences were observed in growth and development between the groups. No osteoartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Radiological confirmation of arthropathy using MR1 was positive in two studies involving six cystic fibrosis patients, who had joint effusions, abnormal thickness of articular cartilage, non-homogeneous structure of cartilage or altered two-layer appearance of cartilage 79 91. In addition to clinical examination and radiological investigation, seven studies (531 cases and 674 controls) investigated the effects of ciprofloxacin on growth of patients after following up the patients for 6–50 months 28 32 33 63 75 109 116. None of these studies found any significant difference in growth of the ciprofloxacin exposed patients compared with the control arm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiological confirmation of arthropathy using MR1 was positive in two studies involving six cystic fibrosis patients, who had joint effusions, abnormal thickness of articular cartilage, non-homogeneous structure of cartilage or altered two-layer appearance of cartilage 79 91. In addition to clinical examination and radiological investigation, seven studies (531 cases and 674 controls) investigated the effects of ciprofloxacin on growth of patients after following up the patients for 6–50 months 28 32 33 63 75 109 116. None of these studies found any significant difference in growth of the ciprofloxacin exposed patients compared with the control arm.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of 23 controlled studies (7 controlled studies were excluded because ciprofloxacin or another fluoroquinolone was administered in the comparator arm) comprising 6481 cases and 17 441 controls showed that there is a 57% increased risk of arthropathy in patients who received ciprofloxacin compared to the comparator arm (OR 1.57, 95% CI 1.26 to 1.97) 13 15–19 2833 63 75 76 79 101 103 105 109 111 112 116. Further analysis of five controlled studies that included only cystic fibrosis patients (227 cases and 391 controls) estimated a 67% increased risk of arthropathy (OR 1.67, 95% CI 1.13 to 2.45) 17 19 79 101 105…”
Section: Resultsmentioning
confidence: 99%
“…Little is known about FQ safety in newborns and infants. 46,47 However, laboratory findings in juvenile animals indicated that younger animals were at higher risk of cartilage damage. [5][6][7] Therefore, future studies perhaps should focus on this age group with long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the potential to cause harm exists, further study is needed before the fluoroquinolones can be recommended for routine use in paediatric patients. A study by Martell et al (232) assessed whether growth of preterm infants was affected by administration of a fluoroquinolone. This study reported lower weight and smaller head circumference in the fluoroquinolone-treated individuals, relative to a reference group.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…This study reported lower weight and smaller head circumference in the fluoroquinolone-treated individuals, relative to a reference group. It was not clear whether this was due to treatment with a fluoroquinolone or another variable such as the severity of illness (232).…”
Section: Adverse Effectsmentioning
confidence: 99%